Communicative Language Teaching in the Moroccan EFL Classroom - AIT HATTANI, Hanae (Yayasan Visi Intan Permata, 2018)
Today, communities are increasingly facing rapid and profound changes and tensions that affect the social, economic, and political aspects of life. The role of education has also become questionable in the millennial era. A matter of fact, 21st century education requires a gradual shift in curriculum construction focusing on the transferable competencies that learners need to develop in instructional settings. In today’s knowledge-based, types of skills and competencies that students need to gain are different from in the past. Emphasizing the communicative competence is one of the most influential developments in language education. The implementation of communicative activities in EFL/ESL classroom prepares learners to use English in the world beyond based on their own needs, interests, and opportunities, and perform in an atmosphere of expression, interpretation, and negotiation of meaning from psycholinguistic and socio-cultural perspectives. Communicative language teaching (CLT) refers to both processes and goals in classroom learning. It is one of the most influential theoretical developments in language education as it helps redefine the objectives of foreign and/or second language instruction. This paper looks at the phenomenon of communicative language teaching (CLT) in the Moroccan EFL curriculum. It aims to study how CLT has been interpreted and implemented in various contexts examining teachers’ attitudes. The data is gathered using semi-structured interview with EFL secondary level teachers. Based on the findings, respondents reflected positive attitudes showing that the use of CLT approach does enhance oral competency among students as well as learner-autonomy. However, teachers confirm that the EFL curriculum is barely emphasizing communication skills, which requires a curriculum reform and redesign in order to represent the 21st century requirements and values.